Development of an Ewuh Pakewuh Scale Instrument Based on Javanese Cultural Values - Widia Wahyu Rahmawati; Lisnawati Ruhaena; Muhammad Roby; Annisa Kholila (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
The ewuh pakewuh culture in Javanese society reflects a feeling of hesitation or reluctance to express opinions in order to maintain social harmony. This study aims to develop a measurement instrument or ewuh pakewuh scale based on Javanese cultural values that meets the criteria of validity and reliability. The research process involved both qualitative and quantitative stages. The qualitative stage aimed to collect data on the concept of ewuh pakewuh through open-ended questionnaires. A total of 41 respondents were involved to explore the cultural meaning of the concept, which resulted in six conceptual aspects: social interaction, social norms, hierarchy, communication, social conformity, and self-expression. Based on these aspects, 35 items were constructed and tested in the quantitative phase. The quantitative stage involved 763 respondents and was analyzed using Exploratory Factor Analysis (EFA). The results identified three main dimensions: self-expression, indirect social communication, and conformity to hierarchy. The scale showed high reliability (Cronbach’s Alpha > 0.89; KMO = 0.951). These findings indicate that the developed scale is construct-valid and reliable for measuring ewuh pakewuh tendencies within the Javanese cultural context.Budaya ewuh pakewuh dalam masyarakat Jawa mencerminkan perasaan sungkan atau segan dalam menyampaikan pendapat demi menjaga harmoni sosial. Penelitian ini bertujuan mengembangkan alat ukur atau skala ewuh pakewuh berbasis nilai budaya Jawa yang memenuhi kriteria valid dan reliabel. Tahapan penelitian yang dilakukan mencakup penelitian kualitatif dan kuantitatif. Penelitian kualitatif bertujuan mengumpulkan data tentang konsep ewuh pakewuh yang dilakukan melalui angket terbuka. Responden angket terbuka sebanyak 41 responden untuk digali tentang makna budaya dan menghasilkan enam aspek: interaksi sosial, norma sosial, hierarki, komunikasi, konformitas sosial, dan ekspresi diri. Berdasarkan enam aspek ini dibuat 35 aitem untuk diuji cobakan dalam penelitian kuantitatif. Selanjutnya, Tahap kuantitatif melibatkan 763 responden dan dianalisis menggunakan Exploratory Factor Analysis (EFA). Hasil menunjukkan tiga dimensi utama, yaitu ekspresi diri, komunikasi sosial tidak langsung, dan konformitas terhadap hierarki. Skala menunjukkan reliabilitas tinggi (Cronbach’s Alpha > 0,89; KMO = 0,951). Hasil ini menunjukkan bahwa skala yang dikembangkan valid secara konstruk dan reliabel untuk mengukur kecenderungan ewuh pakewuh dalam konteks budaya Jawa.